-3(7+n)=33

Simple and best practice solution for -3(7+n)=33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(7+n)=33 equation:


Simplifying
-3(7 + n) = 33
(7 * -3 + n * -3) = 33
(-21 + -3n) = 33

Solving
-21 + -3n = 33

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '21' to each side of the equation.
-21 + 21 + -3n = 33 + 21

Combine like terms: -21 + 21 = 0
0 + -3n = 33 + 21
-3n = 33 + 21

Combine like terms: 33 + 21 = 54
-3n = 54

Divide each side by '-3'.
n = -18

Simplifying
n = -18

See similar equations:

| 2y+1=-11 | | 2(140g+35)= | | y=6x+33+9 | | 24x/12-8x | | 7(40g+10)= | | 280g+70= | | 2(a+1)-(a-2)=0 | | x-5x-4=0 | | x^3-6*x-2=0 | | 5i(6-8i)= | | (x/-12)=-156 | | 2x-7=3(2-3x) | | 23(x-2y)= | | 6(7x-5y)= | | 8w=6/7= | | 30x-42y= | | 38=2+6m | | 23(2x-y)= | | G^2+4g+4= | | 23y-46x= | | 3p+12=99 | | -2c-36=2c+16 | | n^2-10n=23 | | 7x=56x | | 2x-12=2x+3 | | 3(x+6)+2x=10 | | -3(4y+2)-6y=-10y-22 | | 23x-46y= | | y=48.149(x)-2000000 | | 4x^2+35x+24= | | B=22.5n+27.5 | | 4.019=t-6.11 |

Equations solver categories